Growth potential of Listeria monocytogenes in probiotic cottage cheese formulations with reduced sodium content. (March 2016) - Jesus, Ana Laura T.; Fernandes, Meg S.; Kamimura, Bruna A.; Prado-Silva, Leonardo; Silva, Ramon; Esmerino, Erick A.; Cruz, Adriano G.; Sant'Ana, Anderson S.
Abstract: In this study the growth potential (δ) of Listeria monocytogenes in six formulations of probiotic ( Lactobacillus acidophilus and Bifidobacterium lactis ) reduced-sodium cottage cheese containing or not NaCl, combined with KCl and/or MgCl2 stored under different temperature conditions was assessed. Reduced-sodium cottage cheeses were inoculated with L. monocytogenes (approximately 10 3  CFU/g) and then stored at 4 °C (I), 30% of the shelf life at 4 °C and the remaining 70% at 12 °C (II) and 12 °C (III) for 28 days. A growth potential ( δ ) above 0.5 log CFU/g indicated that the formulation was capable of supporting the growth of L. monocytogenes . The growth potential ( δ ) of L. monocytogenes at 4 °C (I) was between 0.5 and 0.8 log CFU/g. Higher growth potentials (1.1–1.6 log CFU/g) were observed when the cottage cheeses were stored for 30% of the shelf life at 4 °C followed by storage for 70% at 12 °C (II). In the scenario III (28 days at 12 °C), L. monocytogenes was only able to grow in the formulation with 100% NaCl and no probiotics (F1), while in F2–F6 (probiotic formulations with different combinations of NaCl, KCl, MgCl2 ) the populations of this bacterium were below the quantification level (< 1 log CFU/g). Independent of the storage scenarios studied, strict conditions of hygiene during processing and use of raw materials of excellent microbiological quality are key-factors for ensuring the safety of this product as L. monocytogenes will be able to grow at low storage temperature. Highlights: Growth of Listeria monocytogenes in probiotic reduced-sodium cottage cheeses (PRSC) was studied. Six formulations of PRSC containing different combinations of NaCl, KCl and MgCl2 were studied. Salt types/concentrations in cottage cheeses affected the survival of probiotics. L. monocytogenes growth was affected by salts depending on the storage conditions.